2006
DOI: 10.1007/s00330-006-0426-8
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos Surveillance Program Aachen (ASPA): initial results from baseline screening for lung cancer in asbestos-exposed high-risk individuals using low-dose multidetector-row CT

Abstract: The purpose of this study was to assess the prevalence of lung cancer in a high-risk asbestos-exposed cohort using low-dose MDCT. Of a population of 5,389 former power-plant workers, 316 were characterized as individuals at highest risk for lung cancer according to a lung-cancer risk model including age, asbestos exposure and smoking habits. Of these 316, 187 (mean age: 66.6 years) individuals were included in a prospective trial. Mean asbestos exposure time was 29.65 years and 89% were smokers. Screening was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 39 publications
0
36
1
2
Order By: Relevance
“…Overall, the study showed some inaccuracy in the diagnostic workup of suspicious findings and incongruity in their treatment [20]. More recently, two small studies were conducted, each including an asbestos-exposed cohort of Ͻ200 individuals [21,22]. Notably, in all three cases, study participants were mostly smokers/former smokers (97%, 99%, and 100%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the study showed some inaccuracy in the diagnostic workup of suspicious findings and incongruity in their treatment [20]. More recently, two small studies were conducted, each including an asbestos-exposed cohort of Ͻ200 individuals [21,22]. Notably, in all three cases, study participants were mostly smokers/former smokers (97%, 99%, and 100%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Although not proven, such nodules may be best found with multi-slice CTs by using thin cuts. In a multi-slice CT study with 0.75 mm collimation, 1 mm slice reconstruction and 0.5 mm increment 163 screened persons out of 187 (87 %) had one or more nodules, out of which 75 % fell in the smallest category, 3-5 mm in size [12]. All lung cancer in their series had a diameter of 15 mm or more.…”
Section: Discussionmentioning
confidence: 99%
“…From 2002 to 2009, the results of some lung cancer screening trials with LDCT on asbestos-exposed workers were published (29)(30)(31)(32)(33)(34). Unfortunately, in these studies CT image acquisition and reconstruction algorithms are different as well as technical parameters (mA, slice thickness, reconstruction interval, additional HRCT slices, etc.…”
Section: Ldct Lung Cancer Screening In Asbestos-exposed Workersmentioning
confidence: 99%
“…); furthermore, the criteria to determine a positive test are not homogeneous. Most of all use ELCAP, I-ELCAP criteria (22,23) or a modification of these (29,31,32,35) to determine a positive test for non-calcific nodule; in other trials the presence of pleural abnormalities is a criterion considered for a positive test (29)(30)(31)(32), but the definitions of pleural involvement and subsequent work-up are various and not always included in the protocol study.…”
Section: Ldct Lung Cancer Screening In Asbestos-exposed Workersmentioning
confidence: 99%